Música y su impacto en el desarrollo cognitivo de los niños de Educación Inicial I - Garces Carpio, Belén Elizabeth (2025)
The research was carried out at the 14 de Junio Basic Education School located in the City of Vinces, with the objective of determining the impact of music on the cognitive development of children in Early Education I. There are various problems such as lack of attention, memorization, communication and problem solving that impact children's academic development, as well as the lack of musical instruments such as rattles, tambourines, among others. This study is presented through theoretical bases through bibliographic sources. The methodology used has a qualitative approach, having a descriptive level, with a documentary and field design, in addition, the technique used in this study is interview and observation with their respective instruments which are the questionnaire with open questions and the data sheet. observation with different parameters to study, intended for a sample of 40 students and a teacher. The first stage of a boy or girl's life is of great importance since both parents and teachers must deal with the cognitive part, which is what allows them to reach and manipulate the information their brain receives and then transform it into meaningful learning. For their daily lives, music will be used as a strategic resource, reaching children in different ways, especially encouraging them to develop the skills and abilities they possess.